SIRT6 Widely Regulates Aging, Immunity, and Cancer - Li, Yunjia; Jin, Jing; Wang, Yi (Frontiers in Oncology, 2022)
SIRT6 is a member of the Sir2-like family in mammals. Recent structural and biochemical studies have characterized SIRT6 as having deacetylation, defatty-acylation, and mono-ADP-ribosylation activities, which determine its important regulatory roles during physiological and pathological processes. This review focuses mainly on the regulatory functions of SIRT6 in aging, cancer, and, especially, immunity. Particular attention is paid to studies illustrating the critical role of SIRT6 in the regulation of immune cells from the viewpoints of immunesenescence, immunometabolism, and tumor immunology. Owing to its role in regulating the function of the immune system, SIRT6 can be considered to be a potential therapeutic target for the treatment of diseases.